2008
DOI: 10.1021/la800800m
|View full text |Cite
|
Sign up to set email alerts
|

AFM Studies of Solid-Supported Lipid Bilayers Formed at a Au(111) Electrode Surface Using Vesicle Fusion and a Combination of Langmuir−Blodgett and Langmuir−Schaefer Techniques

Abstract: Atomic force microscopy (AFM) has been used to characterize the formation of a phospholipid bilayer composed of 1,2-dimyristyl-sn-glycero-3-phosphocholine (DMPC) at a Au(111) electrode surface. The bilayer was formed by one of two methods: fusion of lamellar vesicles or by the combination of Langmuir-Blodgett (LB) and Langmuir-Schaefer (LS) deposition. Results indicate that phospholipid vesicles rapidly adsorb and fuse to form a film at the electrode surface. The resulting film undergoes a very slow structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
94
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 104 publications
16
94
1
Order By: Relevance
“…The layer was formed upon liposome attachment to the gold surface. As will be shown in the results, this layer can consist either of an ILL or of a SLB, depending on the gold surface roughness and experimental conditions, in agreement with previous reports [26][27][28][29]. For the sake of simplicity, this layer will be termed "sensing layer", regardless of its structure.…”
Section: Electrochemical Measurementssupporting
confidence: 57%
See 1 more Smart Citation
“…The layer was formed upon liposome attachment to the gold surface. As will be shown in the results, this layer can consist either of an ILL or of a SLB, depending on the gold surface roughness and experimental conditions, in agreement with previous reports [26][27][28][29]. For the sake of simplicity, this layer will be termed "sensing layer", regardless of its structure.…”
Section: Electrochemical Measurementssupporting
confidence: 57%
“…However, it is important to notice that the gold surface of the QCM-D sensors is not as smooth as that employed in section 3.1. Previous reports have shown that liposome rupture and spreading does not occur on QCM-D gold sensors [28], leading to the formation of an ILL, in contrast to what is observed in atomically smooth gold surfaces [26,27,35]. EQCM-D measurements enabled following the formation of the sensing layer both by monitoring the changes in frequency and dissipation of the sensor crystal, as well as by the appearance of the UQ redox signal in CV.…”
Section: Formation and Characterization Of The Sensing Layermentioning
confidence: 99%
“…DMPC is broadly used for preparation of biomimetic membranes. It was chosen as a model system since the structure of gold supported bilayers of this particular lipid are very well characterized using photon polarization modulation infrared reflection absorption spectroscopy (PMIRRAS) [25,26], atomic force microscopy (AFM) [27], and neutron reflectivity (NR) [28]. Cholesterol is a common component of the membranes of eukaryotic cells [29].…”
Section: Introductionmentioning
confidence: 99%
“…Vesicles spreading and combined Langmuir-Blodgett and Langmuir-Schaefer (LB-LS) transfer are predominantly used to fabricate lipid bilayers on electrode surfaces [8, 9, 31-34, 88, 118, 124]. Numerous electrochemical, in situ PM IRRAS and AFM studies show clearly that pure phospholipid bilayers prepared on the Au electrode surface by vesicles spreading have poorly defined structure [8,9,32,120,125]. Defects are present in these bilayers and the hydrocarbon chains at phospholipid molecules adapt a large tilt with respect to the electrode surface [8,120].…”
Section: Application Of In Situ Pm Irras For the Determination Of Thementioning
confidence: 99%